Measuring forces between two single actin filaments during bundle formation - Streichfuss, Martin; Erbs, Friedrich Philipp Joachim Erich; Uhrig, Kai; Kurre, Rainer; Clemen, Anabel E.-M.; Böhm, Christian H. J.; Haraszti, Tamás; Spatz, Joachim P. (Nano letters, 2011)
Bundles of filamentous actin are dominant cytoskeletal structures, which play a crucial role in various cellular processes. As yet quantifying the fundamental interaction between two individual actin filaments forming the smallest possible bundle has not been realized. Applying holographic optical tweezers integrated with a microfluidic platform, we were able to measure the forces between two actin filaments during bundle formation. Quantitative analysis yields forces up to 0.2 pN depending on the concentration of bundling agents.
Gesehen am 24.10.2022